Biobanking marine biodiversity in the Arctic - Chernikhova, Darya; Basran, Charla J. (Frontiers in Marine Science, 2025)
Biorepositories, or biobanks, are vital to marine science. Their collections safeguard biological knowledge, enable follow-up studies and reproducibility confirmations, and help extend ecological baselines. Biorepository networks and data portals aggregate catalogs and facilitate open data and material exchange. Such integrations enrich contextual data and support holistic ecosystem-based research and management. In the Arctic, where researchers face vast scales, rapidly changing ecosystems, and limited resampling opportunities, biobanking builds capacities. However, marine and polar biodiversity remains underrepresented in collections. Heterogeneous methodologies and documentation practices hinder data integrations. And open science faces high institutional and cultural barriers. Here, we explore the potential of biobanking to amplify the impact of individual marine studies. We address gaps in standardization and vouchering and suggest improvements to funding and publishing models to incentivize collaboration. We bring together calls for biobanking advancements from diverse perspectives and provide examples of expeditions, databases, specimen collections, and standards. The general analysis is illustrated with two case studies, showcasing the range of the field: inclusion of citizen science observations in cetacean monitoring, and preservation of specimens in environmental microbiome studies. In the former, we suggest strategies for harmonizing data collection for inclusion in global databases. In the latter, we propose cooperative field collection and intact living microbiome (complex microbial community) cryopreservation. Our perspective frames biobanking as a cooperative research strategy, essential to accelerating science under the current climate change-related pressures. We advocate for international investment as the precautionary approach to academic and conservation stewardship of the Arctic biodiversity heritage.